Methodology for the evaluation of the residual impact on landscape due to an opencast coal mine in Laciana Valley (Spain) (2015)
This work describes a methodology to evaluate the landscape residual impact of an opencast coal mine in Laciana Valley (Spain), applying a landscape impact index that evaluates: the loss of visual quality of the landscape due to the extractive activity and its visual influence, depending on the visual absorption capacity of the environment, the degree of restoration of the upset areas, and its visibility from the zones most frequented by the population. Final results of the evaluation show severe and moderate impacts on landscape depending on the landscape unit. The landscape impact index is shown as a useful tool that can be applied to restoration designs, environmental vigilance plans and recovery of areas degraded by mining activity.